ANALISIS POTENSI HIDRO KINETIK DI SUNGAI CISADANE UNTUK PENGEMBANGAN TURBIN ULIR SCREW SKALA KECIL - Nugraha, Hari Din; Laksanawati, Ellysa Kusuma; Suhendra, Dedi (Universitas Muhammadiyah Tangerang, 2023)
Energy is currently decreasing due to excessive use of fossil energy in all fields. Issues about global warming, air pollution and the effects of greenhouse gases have also encouraged progress in research on more environmentally friendly sources of electrical energy (Revelation, 2018). Calculation of Measured Discharge To obtain discharge data, direct measurements were carried out at the Air Anak River PLTMH location. The method used to measure discharge is by making stakes on both sides of the river bank. Then tie a rope on both sides of the stake so that the rope stretches from one bank of the river to the other, so that the width of the river can be measured. After obtaining the width of the river, points were made every 25 cm and at each point the flow speed was found using a current meter and the depth was measured. Discussion of the results of the analysis of hydrokinetic energy potential in the Cisadane River can involve various aspects, including the data that has been collected, analysis methods, and the implications in the context of sustainable energy development. The following are the steps that may be involved in discussing the results of the hydrokinetic energy potential analysis in the Cisadane River to obtain a water discharge of around 0.14 liters/minute and obtain a hydropower potential of 2.5 m3/s.